2012
DOI: 10.1093/jjco/hys145
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Administration of Diclofenac Sodium Affects Renal Function After Laparoscopic Radical Nephrectomy in Elderly Patients

Abstract: Objective: Non-steroidal anti-inflammatory drugs decrease the glomerular filtration rate. However, few studies have been conducted on renal function in patients treated with nonsteroidal anti-inflammatory drugs during the first week after laparoscopic radical nephrectomy. The purpose of this study is to determine whether short-term administration of non-steroidal anti-inflammatory drugs during the first week after laparoscopic radical nephrectomy is a risk factor for impaired renal function. Methods: Renal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…raising in the renal biomarkers. The induced AKI in this study as well showed significant reduction in the estimated GFR which was due to the development of acute tubular necrosis and glomerular damage since; Tomohiro et al, 34 exposed that short-term administration of diclofenac leads to proximal renal tubular damage and significant glomerular damage due to potential inhibition of renal prostaglandins which per se reduce renal blood flow and causing renal ischemia. BMI of the experimental rats was higher compared with the control group this might due to daily body weight gain or fluid retention which caused by renal damage.…”
Section: Originalsupporting
confidence: 54%
“…raising in the renal biomarkers. The induced AKI in this study as well showed significant reduction in the estimated GFR which was due to the development of acute tubular necrosis and glomerular damage since; Tomohiro et al, 34 exposed that short-term administration of diclofenac leads to proximal renal tubular damage and significant glomerular damage due to potential inhibition of renal prostaglandins which per se reduce renal blood flow and causing renal ischemia. BMI of the experimental rats was higher compared with the control group this might due to daily body weight gain or fluid retention which caused by renal damage.…”
Section: Originalsupporting
confidence: 54%
“…Taken into account the plenty of polyunsaturated fatty acids in renal tissues, DS specifically invades the renal microenvironment to induce oxidative and nitrosative stress compromising the renal cytological patterns, blood flow in addition to glomerular capillary ultrafiltration coefficient (Aycan et al, 2018;Garcia-Cohen et al, 2000;Kubo et al, 1997). The renal microvasculature is constricted and perfusion is impaired owing to the ability of DS to suppress generation of vasodilator prostaglandins in the kidneys (Mizuno et al, 2012). This pathological condition promotes renal tubular damage and impairs regenerative ability, which is the leading cause of renal interstitial fibrosis (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings illustrated that induced AKI was associated with a significant reduction in the eGFR due to the development of acute tubular necrosis and glomerular damage since; high dose of diclofenac leads to AKI due to inhibition of renal prostaglandins. [17]…”
Section: Discussionmentioning
confidence: 99%